2020
DOI: 10.1097/mej.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Neurological outcomes after an out-of-hospital cardiac arrest among people living in high-rise buildings in South Korea

Abstract: Objective Living in high-rise buildings may cause delays in reaching a hospital after an out-of-hospital cardiac arrest. This study aimed to compare neurological outcomes in people who had had an out-of-hospital cardiac arrest, according to their floor of residence. Methods We conducted a retrospective study of 1541 patients aged ≥20 years who had out-of-hospital cardiac arrest between 1 October 2015 and 30 June 2018, using data from a central registry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A further seven articles were removed after review of full texts. Finally, 23 articles were included in the scoping review [ 4 , 5 , 6 , 7 , 8 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The characteristics of included studies are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further seven articles were removed after review of full texts. Finally, 23 articles were included in the scoping review [ 4 , 5 , 6 , 7 , 8 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The characteristics of included studies are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported similar findings of the negative impact of higher floors on neurologically intact survival measured at hospital discharge or at 1 month. Kobayashi et al and Sohn et al both reported significantly lower unadjusted rates of neurologically intact survival for OHCA patients living 3 floors or higher above ground [ 25 , 30 ]. Choi et al found that patients residing on a high floor of 3 storeys or more had significantly lower unadjusted rates of neurologically intact survival compared to if the OHCA took place in a public area [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual incidence of Out of Hospital Cardiac Arrest (OHCA) is not exactly known and varies largely between countries from 28 to 160 per 100 000 inhabitants [1]. Quality of early cardiopulmonary resuscitation (CPR) by bystanders and ambulance staff can lead to a significant improvement in Return of Spontaneous Circulation (ROSC) and good neurological outcomes [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Quality of early cardiopulmonary resuscitation (CPR) by bystanders and ambulance staff can lead to a significant improvement in Return of Spontaneous Circulation (ROSC) and good neurological outcomes [2,3].…”
Section: Introductionmentioning
confidence: 99%